Personal Trajectories of Participation across Contexts of Social Practice - Dreier, Ole (Outlines. Critical Practice Studies, 1999)
In discussion about basic theoretical approaches in a non-Cartesian psychology several candidates for a key concept were proposed, such as action, activity, relation, dialogue and discourse. None of these concepts, however, sufficiently grounds psychological theories of individual psychology in social practice. To accomplish this we need to conceptualize subjects as participants in structures of ongoing social practice. In this paper I argue why and address issues of subjectivity as encountered by persons in their participation in complex structures of social practice. I introduce the concept of personal conduct of life and life-trajectory as elaborations of my theory. And I discuss this theoretical approach and show what is at stake in developing it by comparing it to similar approaches in the current literature on the person, self, and identity.